Reconnection-less OTA-based Biquad Filter with Electronically Reconfigurable Transfers - Sotner, Roman; Petrzela, Jiri; Jerabek, Jan; Dostal, Tomas (Elektronika ir Elektrotechnika, 2015)
This paper deals with operational transconductance amplifiers (OTAs) -based active voltage-mode biquad filter with electronically reconfigurable transfer functions. Due to utilization of the very favourable active devices, this design is ready for immediate CMOS design. Presented filtering solution contains four active elements where each of them is directly used for reconnection-less change of transfer function or modification including electronic control of quality factor and tuning. The filter offers availability of all-pass, high-pass, band-pass, band-reject transfer response and special transfers as high-pass with zero and low-pass with zero. Measurement results based on utilization of diamond transistors confirmed expected behaviour of the circuit. DOI: http://dx.doi.org/10.5755/j01.eee.21.3.10205